Violence and language. Reflections on Emanuele Severino’s work - Ordoñez Roig, Vicente (Revista de Filosofía, 2012)
The author examines thoroughly a basic problem of emanuele Severino metaphysics: the implicit connection between violence and language. He analyzes several important distinctions, but he specially emphasizes the main aspects of his work, such as the will to power, the metaphysics as place of nihilism or the Plato’s word that takes to the light the sense of the thing on having put it as an epamphoterízein. The author concludes that in Severino’s thought violence and language are mixed up in the common substratum from which our civilization rises.
Keywords: nihilism; metaphysics; interpretation; power; conviction